2018
DOI: 10.1097/iae.0000000000001782
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Frequency of Intravitreal Aflibercept Versus Bevacizumab for Macular Edema Secondary to Central Retinal Vein Occlusion

Abstract: Both aflibercept and bevacizumab are comparably effective for treatment of macular edema secondary to central retinal vein occlusion without significant complications. However, the burden of frequent intravitreal injections could be significantly reduced when using aflibercept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…; Lotfy et al. ) and a ‘low impact’ group ( N = 7) with IF ≥ 2 and <3 (Cekic et al. ; Moradian et al.…”
Section: Resultsmentioning
confidence: 99%
“…; Lotfy et al. ) and a ‘low impact’ group ( N = 7) with IF ≥ 2 and <3 (Cekic et al. ; Moradian et al.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the visual gains of the first year reduced in a similar fashion to COPERNICUS at the 18-month study end-point [7,8,11]. Since then, other trials have investigated different loading periods, follow up intervals and more recently, treat-and-extend protocols [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 91%
“…58 A RCT comparing aflibercept and bevacizumab on a one plus pro re nata basis found that those in the aflibercept arm required fewer injections at 12 months. 59 The COMRADE-C trial was a Phase IIIb, multicentre, double-masked, randomised clinical trial that compared a ranibizumab loading phase followed by pro re nata dosing with 0.7 mg of dexamethasone, given only at baseline, for MO due to CRVO, and showed a favourable outcome with ranibizumab. 60 A 2019 systematic review 61 evaluating the effectiveness and adverse effects of ranibizumab, aflibercept and bevacizumab in three common retinal conditions, including RVO, reported that none of the 17 included studies showed a clinically important difference (i.e.…”
Section: Evidence Update Post Leavo Initiationmentioning
confidence: 99%
“…It was not possible to perform a safety meta-analysis because of the lack of comparative outcome data for anti-VEGF therapy in CRVO. Two other comparative studies were completed during LEAVO: the multicentre SCORE2 27 clinical trial, which compared aflibercept and bevacizumab, given by mandated monthly injection over 6 months, and a small comparative study 59 of aflibercept versus bevacizumab in 50 patients with MO due to CRVO who were followed up for 12 months. The latter trial did not publish any tabulated AE data and was discounted.…”
Section: Safety Meta-analysismentioning
confidence: 99%